The Stroll of Miss M** Kr*** (now Mrs. Sk...) or the Surroundings of Vilnius. Published, translated and the foreword written by Domininkas Burba - Burba, Domininkas (Literatūra, 2018)
[tekstas lietuvių ir rusų kalbomis]